Late Onset and Protracted Course of Steroid Refractory Chronic Graft-versus-Host Disease - Gursel Gunes; Haluk Demiroglu; Hakan Goker; Umit Yavuz Malkan; Eylem Eliacik; Okan Yayar; Yahya Buyukasik (Case Reports in Hematology)
Chronic graft-versus-host disease (cGVHD) is one of the most important causes of morbidity and mortality after allogeneic hematopoietic stem cell transplantation (aHSCT). Occurring in 30% to 70% of patients, cGVHD has a median time to onset of 4 to 6 months and most cases present within 2 years after aHSCT. Here, we present a patient transplanted at the age of 55 who developed refractory cutaneous cGVHD more than 5.5 years after aHSCT.